Magnetic properties of poly(3-hexylthiophene) - de Paula, Fernando Rogério [UNESP]; Walmsley, L. [UNESP]; Pereira, E. C.; De Oliveira, A. J A (Elsevier B.V., 2008)
A room temperature ferromagnetic phase is observed in samples of poly(3-hexylthiophene) partially doped with ClO (4) over bar. The magnetic behavior presents a strong dependence on the sample preparation conditions, in particular, a dependence with the final potential of the sample after reduction. The origin of the ferromagnetism is proposed to be associated with interactions between spin 1/2 polarons formed in the polymeric chain upon doping. The dependence of saturation and spontaneous magnetization as the function of the final potential after reduction shows a way to control the magnetic properties of this polymer. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: ferromagnetism; conducting polymers; poly(3-hexylthiophene)